Perencanaan Ulang Usaha Pelaku UMKM Kecamatan Sidayu, Kabupaten Gresik - Hadi Ismanto; Vembri Aulia Rahmi (Lembaga Pengembangan Kinerja Dosen, 2025)
Business re-planning is an effort to reorganize a business that has been run with structured governance. MSME actors cannot be separated from various business challenges and obstacles that can affect the growth rate of their business. Business practices for micro entrepreneurs are mostly operated without careful planning. Meanwhile, the business world is growing widely and competition is high. Some MSMEs combine business needs with family interests and result in achieving business visions. Business governance, such as: marketing, finance and products by MSMEs is still conventional, so business re-planning is needed to support business sustainability and especially drive the local economy. Community service in Sidayu District was initiated to instill a modern business mindset. The stages of community service begin with coordination, socialization. The target of this community service is aimed at MSMEs in Gresik Regency so that they can improve their understanding of the importance of business re-planning and improve more adaptive business governance skills. Training for MSMEs is not only about theoretical business insights but also a forum for them to consult on business. The follow-up to business training is to provide business mentoring. The implementation aims to accompany MSMEs in making business changes for the better. The community service went smoothly with high enthusiasm from the training participants.